Molecular aspects of renal senescence. Issue 4 (August 2015) - Schmitt, Roland; Susnik, Nathan; Melk, Anette
Abstract : Purpose of review: The aging kidney undergoes profound changes that lead to a reduction in stress resistance and impaired repair capacity. In order to improve the outcome of acute and chronic kidney damage, it is instrumental to understand the mechanisms that cause these changes. Cellular senescence has emerged as an important cellular process that contributes to age-associated kidney changes and chronic kidney disease progression. Recent findings: New mechanistic insights into excessive intracellular glucose, advanced glycation end products and endoplasmatic reticulum stress further support the importance of cellular senescence in the development of diabetic nephropathy. As telomere length of leukocytic DNA is increasingly used as a biomarker to estimate senescence in clinical cohort studies, this review also summarizes the literature on telomere length with respect to the kidney and evaluates the strengths and weaknesses of this methodology. Furthermore, novel findings on the relationships among telomeres, senescence and autophagy are discussed. Summary: Cellular senescence contributes to the decline in renal function during aging and defective regeneration in kidney diseases. Further insight into the underlying molecular mechanisms of senescence will establish a basis for preventive strategies that improve renal stress resistance and regenerative capacity.